Multiculturalism And Internationalization Of Malaysian Educational Instituitions - Honarmand, Ali (2009)
This study integrated these fields and investigated the relationship between theses three strategies area from the perspective of Malaysian students. This study shows that organizational culture and regional culture are directly linked and follow a dynamic system within which the interactions between components shape the behavior of the members and in an international university or college with a diverse cultural system for students and staff, understanding of these dynamics is a critical point and mangers, executives and all practitioners must respect to the different aspects of a cultural diversity in an organization.